Evaluation of Pain Tolerance Threshold Following Administration of Anti-TNF-α in REM Sleep-deprived Male Wistar Rats - Mohammadjavad Hoseinpourfard; Mohammad Nasehi; Mohammad-Reza Zarrindast; Morteza Izadi; Mohammad Nami (Iranian Journal of Neurosurgery, 2021)
Background and Aim: The level of Tumor Necrosis Factor-alpha (TNF-α) changes by REM sleep deprivation. TNF-α is a known biomarker of REM sleep deprivation (RSD). Prior studies have shown that any alteration in REM sleep can increase the amount of TNF-α. Accordingly, the Pain Tolerance Threshold (PTT) is believed to be increased in patients with insomnia after using anti-TNF-α or Infliximab (IFX). The present study aims to demonstrate the effect of IFX and its importance in the pain management of hospital inpatients.